Redesign Meja Las di CV. Cipta Karya - Nurjannah; Aldo Elandri Putra (Universitas Sriwijaya, 2022)
The table is one of the tools used for welding in CV. Cipta Karya. The table used is a self-made table without using a standard size, so sometimes in its use the operator often experiences problems such as having to bend over and a bad position. The redesign of the welding table uses an anthropometric approach with the NIDA method, with the aim of designing an ergonomic welding table so that the operator feels comfortable and safe while working. The results of the redesign of the welding table are with an extension table to adjust the workpiece used, a toolbox storage area, table pores to absorb smoke during welding, and there is a smoke sensor as a safety device for the operator. The size of the welding table that has been redesigned, without the extension table, is 171x82x107 cm, while the size of the welding table with the extension table is 250x120x107 cm.